Effect of Prone Position with Right-sided Head Rotation to Endotracheal Cuff Pressure: A Prospective Observational Study - Phanpaisan, Chininthon (Thai Journal of Anesthesiology, 2021)
Background: Some surgical procedures, for example, spine surgery must be performed in prone position. Prone position causes many physiological changes. The position of endotracheal tube might be displaced. Furthermore, the cuff pressure may change from the original pressure applied in the supine position. Objective: To assess the effect of prone position with right-sided head rotation to endotracheal cuff pressure. Methods: We conducted a prospective observational study of 20 adult patients underwent lumbar spine surgery in prone position. The patients who had cervical spine pathology and limited neck motion were excluded. After the patient was positioned prone with right-sided head rotation, the endotracheal cuff pressure was measured every 5 minutes. The time period that cuff pressure exceeded 30 cmH2 O was recorded. The pressure was adjusted within the range of 20-30 cmH2 O. Results: There were group of 10 patients (50%) who had cuff pressure exceeded 30 cmH2 O at 5 minutes and other group of 10 patients (50%), which cuff pressure gradually increased to more than 30 cmH2 O after 5 minutes. There were not significantly differences of demographic data in both groups.